Taxonomy confirmation of Puntius cf. binotatus from Gunung Tujuh Lake, Jambi, Indonesia based on Cytochrome Oxidase-I (COI) gene - DEWI IMELDA ROESMA; DJONG HON TJONG; WILA KARLINA; DYTA RABBANI AIDIL (Biodiversitas Journal of Biological Diversity, 2019)
Roesma D. I, Tjong D. H, Karlina W, Aidil D. R. 2019. Taxonomy confirmation of Puntius cf. binotatus from Gunung Tujuh Lake based on Cytochrome Oxidase-I (COI) gene. Biodiversitas 20: 54-60. The population of Puntius cf. binotatus Gunung Tujuh Lake in considered as an isolated population which found in the 20-30 meters depth under the water Gunung Tujuh Lake, Sumatra Island. The species often exhibit different phenotypic characters and may genetic characters may also different due to their response to habitat/ecological conditions. Previous study on P. binotatus from several locations in West Sumatra showed the complexity of the genetic and morphological characters. A molecular study using COI gene of P. cf. binotatus from Gunung Tujuh Lake in Sumatera has been conducted to determine the taxonomic status of the fish. The distinct morphological characters of Puntius cf. binotatus is one black spot in the middle of the caudal and the absent of black spot on the base of the anterior dorsal ray. The analysis on COI gene showed that the range of sequence divergences between P. cf. binotatus Gunung Tujuh Lake and other Sumatra P. cf. binotatus is 3.1-7.6% and 4.1% to Barbodes banksi. This value represents the differences at the subspecies level of Barbodes banksi. Therefore Barbodes banksi gunungtujuh is proposed as an appropriate name to P. cf. binotatus Gunung Tujuh Lake.